1986
DOI: 10.1002/jmor.1051880110
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on the histology of the ovotestis in Hypselodoris tricolor and Godiva banyulensis (Gastropoda, Opisthobranchia), with special reference to yolk formation

Abstract: The histology of the ovotestis was studied by light and electron microscopy in two nudibranch gastropod species. While in Hypselodoris tricolor the ovotestis is intimately associated with the digestive gland tissue, the large gonadal mass of Godiva banyulensis is placed freely in the haemocoele. This fact results in great histological differences between both species. As is common among Mollusca, the immature yolk granule in Hypselodoris and Godiva presumably originates from membrane-rich cytoplasmic inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Evidence of incorporation of exogenous yolk precursors through endocytosis in mollusc oocytes has not been widely documented (Jong-Brink et al 1983;Eckelbarger & Blades-Eckelbarger 1989), although it has been reported in one opisthobranch (Eckelbarger & Blades-Eckelbarger 1989), some cephalopods (Selman & Wallace 1978), pulmonates (Hill & Bowen 1976Bottke et al 1982;Jong-Brink et al 1983;Khan & Saleuddin 1983;Bottke 1986), two caenogastropods (Bottke 1973;West 19Sl), and a neritid (Eckelbarger & Young 1997). In contrast, autosynthetic yolk formation has been widely reported and is viewed as the primary yolk-forming process in the Mollusca (Jong-Brink et al 1983;Medina et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of incorporation of exogenous yolk precursors through endocytosis in mollusc oocytes has not been widely documented (Jong-Brink et al 1983;Eckelbarger & Blades-Eckelbarger 1989), although it has been reported in one opisthobranch (Eckelbarger & Blades-Eckelbarger 1989), some cephalopods (Selman & Wallace 1978), pulmonates (Hill & Bowen 1976Bottke et al 1982;Jong-Brink et al 1983;Khan & Saleuddin 1983;Bottke 1986), two caenogastropods (Bottke 1973;West 19Sl), and a neritid (Eckelbarger & Young 1997). In contrast, autosynthetic yolk formation has been widely reported and is viewed as the primary yolk-forming process in the Mollusca (Jong-Brink et al 1983;Medina et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This state is considered to be plesiomorphic. But in many nudibranchs, the gonad spreads over the digestive gland dorsally and is more or less strongly connected to it (Medina et al, 1986). In some genera (e.g.…”
Section: Statocystmentioning
confidence: 99%
“…In bivalves, both single and multiple Golgi complexes occur, for example, a single Golgi complex has been described in Laternula limicola (Kubo 1977), Neotrigonia (Healy 1989), Musculus discors, Nucula sulcata, Dreissena polymorpha (Franzen 1983), Donax (Hodgson et al 1990) and multiple ones in Mytilus edulis (Longo & Dornfeld 1967), Spisula solidissima (Longo & Anderson 1969) and galeommatoid bivalves (Eckelbarger et al 1990). In mollusc classes with modified spermatozoa, for example, Opisthobranchia (Eckelbarger & Eyster 1981;Kubo & Ishikawa 1981;Medina et al 1985), Pulmonata (Takaichi & Dan 1977) and Cephalopoda (Maxwell 1974(Maxwell , 1975, only multiple Golgi complexes occur. Our studies of spermatogenesis in A. entalis provide confirmation of the primitive phylogenetic position of the Scaphopoda.…”
Section: Discussionmentioning
confidence: 99%